TRPML Cation Channels in Inflammation and Immunity - Spix, Barbara; Chao, Yu-Kai; Abrahamian, Carla; Chen, Cheng-Chang; Grimm, Christian (Frontiers in Immunology, 2020)
In 1883, Ilya Mechnikov discovered phagocytes and established the concept of phagocytosis by macrophages. In 1908, he was awarded the Nobel Prize in Physiology/Medicine for his findings, which laid the foundations for today’s understanding of the innate immune response. Only in the 1960s, Max Cooper and Robert Good significantly advanced our understanding of the immune system by demonstrating that B- and T-cells cooperate to regulate the adaptive immune response. Both, innate and adaptive immune response are essential to effectively protect the individual against infectious agents such as viruses, bacterial or insect toxins, or allergens. Innate immune responses occur rapidly upon exposure to noxious or infectious agents or organisms, in contrast to the adaptive immune system that needs days rather than hours to develop and acts primarily on the basis of antigen-specific receptors expressed on the surface of B- and T-lymphocytes. In recent years, it has become evident that endosomes and lysosomes are involved in many aspects of immune cell function such as phagocytosis, antigen presentation and processing by antigen presenting cells, release of proinflammatory mediators, e.g. by mast cells, or secretion of the pore-forming protein perforin by cytotoxic T lymphocytes. Several lysosomal storage disorders (LSDs) have been associated with defects in immune system function or immune system hyperactivity such as Gaucher, Fabry, or Niemann-Pick type C1 disease, mucopolysaccharidoses (MPS), gangliosidosis, or juvenile neuronal ceroid lipofuscinosis (JNCL). Beside accumulating evidence on the importance of endo-lysosomes in immune cell function, recent results suggest direct roles of endo-lysosomal ion channels such as the TRPML channels (mucolipins), which are members of the transient receptor potential (TRP) superfamily of non-selective cation channels, for different aspects of immune cell function. The aim of this review is to discuss the current knowledge about the roles of TRPML channels in inflammation and immunity, and to assess their potential as drug targets to influence immune cell functions. ´